Magnetization Study of Iron Sand from Sabang, Indonesia: The Potential of Magnetic Materials in the Photocatalytic Field - Sri Nengsih; Syahrun Nur Madjid; Mursal Mursal; Rinaldi Idroes; Zulkarnain Jalil (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
The magnetization of iron sand from Anoi Itam beach, Sabang, Indonesia, was investigated through sample testing and synthesis using the co-precipitation method. The purpose of this study is to analyze the magnetic properties of iron sand and review its potential in photocatalytic processes. Before being synthesized, the natural iron sand was separated and milled. The iron sand was dissolved in 37% v/v HCl, stirred, and heated for 30 min. This solution was filtered and precipitated with 6.5 M NH4OH while stirring and heating for 30 min. The magnetite formed was washed repeatedly with distilled water until it reached a normal pH, and then dried. Magnetite characterization tests were performed using XRF, XRD, VSM, and UV-Vis spectroscopy. The test results showed that the iron sand had a high magnetic quality with a concentration of 91.17% after the synthesis process. The resulting magnetite phase structure had a spinal inverse cubic shape, with the highest peak at the Miller index (311). From the VSM test, it is known that the resulting magnetite exists in a soft magnetic form with superparamagnetic groups. From optical absorption, magnetite has a gap energy of approximately 2.8 eV. It can be concluded that the magnetite from Anoi Itam Sabang has potential as a photocatalytic absorbent in the visible light wavelength region. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).